Energy efficiency of photovoltaic façade for different latitudes in Portugal - Sacht, Helenice Maria (2013)
The climate and energy package is a set of binding legislations which aims to ensure the European Union meets its ambitious climate and energy targets for 2020. These targets, known as the "20-20-20" targets, have set three key objectives: a 20% reduction in the EU greenhouse gas emissions, a 20% rise in the share of EU energy consumption produced from renewable resources and a 20% improvement in the energy efficiency. More renewable energies will enable the EU to lower greenhouse emissions and make it less dependent on imported energy. Boosting the industry of renewables will encourage technological innovation and employment in Europe. On this topic, photovoltaic façades are known to be a solution that allows both energy efficiency and environmental performance of buildings. This paper reports on a study of façade systems that have incorporated photovoltaic panels, considering computational simulations for Portugal. The main objective is to analyze the characteristics and parameters that define more efficient systems based on computer simulations carried out by Solterm 5.0. The results show the high potential of the use of the proposed technology in Portugal, especially in the Southern region, because of its latitude. Regarding energy efficiency and environmental performance, inclined polycrystalline silicon solar panels achieved the best results and the most efficient panel was Kyocera KC167G-2, followed by BP 3160. The comparison between simulation results and results provided in the literature shows that the use of computer programs is viable to the analysis of the energy efficiency of photovoltaic systems in façades.